EMPLOYEE PERFORMANCE, WORK DISCIPLINE, AND SERVICE QUALITY AS DETERMINANTS OF CUSTOMER SATISFACTION IN PUBLIC SERVICES - Sutan Martua Hasibuan; Heri Kusmanto; Zulkifli Zulkifli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the impact of employee performance, work discipline, and service quality on community satisfaction in Horas Jaya Market, Pematangsiantar City. The study employs a quantitative methodology with a survey instrument, gathering data from 99 participants selected through random sample approaches. Multiple linear regression was employed to analyze the impact of each independent variable on the dependent variable. The study's results indicated that employee performance and work discipline positively and significantly affected community satisfaction (p < 0.05). Moreover, service quality was the predominant factor affecting community satisfaction (p < 0.01). Simultaneously, these three variables explain 63.7% variation in community satisfaction. The implications of this study show that improving employee performance, strong work discipline, and improving service quality are crucial in creating community satisfaction in traditional markets such as Horas Jaya Market.